Value Management in Project Portfolios: Identifying and Assessing Strategic Value. Issue 5 (October 2014) - Martinsuo, Miia; Killen, Catherine P.
Projects are expected to bring value to their constituents. Value management in project portfolios has centered on the maximization of commercial value and identification of future business prospects. In this study, the goal is increased understanding of the identification and assessment of strategic, non-commercial value in project portfolios. We map the relevant dimensions of strategic value and supplement previous frameworks with the non-commercial aspects. Ecological, societal, and learning values have only been studied conceptually and qualitatively in earlier research. We propose future research on these values in quantitative settings and exploring collective sensemaking as part of project portfolio value management.